Down-Regulation of C3aR/C5aR Inhibits Cell Proliferation and EMT in Hepatocellular Carcinoma. (11th November 2020) - Chen, Bendong; Zhou, Wenyan; Tang, Chaofeng; Wang, Genwang; Yuan, Peng; Zhang, Yawen; Bhushan, Sah Chandra; Ma, Jinlong; Leng, Junzhi
Complement 3a (C3a) and complement 5a (C5a), small cleavage fragments generated by complement activation, has been previously shown to be obviously up-regulated in highly metastatic hepatocellular carcinoma (HCC) cells. However, their functional roles in HCC cells remains unclear. Here, we investigated the biological function of G protein-coupled receptor C3aR/C5aR using small interference RNA in HCC cells. Our data showed that C3aR and C5aR knockdown significantly inhibited the proliferation, migration and invasion of HCC cells using CCK-8, colony formation and transwell assays. Flow cytometry assay showed C3aR and C5aR knockdown induced cell cycle G0/G1 phase arrest and apoptosis in HCC cells. Moreover, we found down-regulation of C3aR/C5aR obviously down-regulated the expression of PCNA, Ki-67 and suppressed the epithelial-mesenchymal transition (EMT) markers (E-cadherin, N-cadherin and vimentin) in HCC cells. Collectively, our data demonstrated that targeting C3aR/C5aR may hold promise for the treatment of HCC.